Economic and Social Consequences of Fringe Benefits - Douglas, Monteath (Relations industrielles / Industrial Relations, 1960)
SummaryIn this article, the Author analyses fringe benefits as fundamental values. According to him, fringe benefits are more than an increase in the pay check; they are an important and permanent element of wage administration structure.